Protection and renovation of public areas in a modernist city – the case of three streets in the historic city centre of Gdynia - Hirsch, Robert; Łozowska, Celina (Protection of Cultural Heritage, 2023)
This article concerns issues related to the preservation and restoration of public space in Gdynia’s city centre, which was designed and built mainly in the 1920s and 1930s. In 2007, a major part of the city centre was entered into the register of monuments asa historic complex of urban architecture. Moreover, in 2015, the area was declared a Monument of History. Protection of a complex of urban architecture covers not only the renovation of historic buildings but also the protection of public spaces that comprise an integral partof the historic complex. Therefore, preservation of the historic shape and design of public space in the centre of Gdynia is one of the city’s key conservation tasks. Since protection of urban space in relatively young historic centres (less than a hundred years old) is a novel issue from the perspective of conservation, it is therefore worth analysing. Issues connected with the protection and restoration of public space in the centre of Gdynia are exemplified by three historic streets, built in the late 1920s and located within a historic complex entered into the register of monuments. They have been the subject of various investments in recent years. The streets differ in terms of their historic condition, renovation requirements, social expectations and investment plans. Already at the developmental stage of investments all these factors have led to different assumptions and approaches, bringing different results in each case.